2022
DOI: 10.1002/aur.2692
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of COVID‐related lockdown on sleep–wake rhythms in adults with autism spectrum disorder compared to the general population

Abstract: COVID-related lockdown led to a radical modification of daily activities and routines which are known to affect sleep. Compared to the general population, participants with autism may be particularly vulnerable to the repercussions of lockdown on sleep, given their intrinsic inflexible adherence to routines and the high overall prevalence of sleep disturbances in this population. The study is a French nation-wide online survey assessing sleep-wake rhythms and behaviors known to affect sleep (daily screen time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The initial systematic literature search yielded 4682 records (Figure 1). The first filtering step resulted in 145 studies, and the second filtering step resulted in a final collection of 46 studies that examined the association between screen time and ASD (Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial systematic literature search yielded 4682 records (Figure 1). The first filtering step resulted in 145 studies, and the second filtering step resulted in a final collection of 46 studies that examined the association between screen time and ASD (Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported on data collected since the COVID-19 pandemic (Table 1). Notably, the research design of all 46 studies was observational: 41 were cross-sectional and 5 were longitudinal . Accordingly, the overall research quality of these studies was determined to be relatively low (according to the GRADE approach) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the pandemic has progressed, the reported impact of COVID-19 on individuals with ASD and their families has been significant [8,[16][17][18]. Specifically, children with ASD have experienced increased mental health issues [1,12,19], a decline in positive social behaviors and other conduct [19], and an increase in sleep disturbances [20,21]. A number of factors may exacerbate these effects [15,22], including the presence of behavioral issues prior to the pandemic [23] and parental stress levels [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Lockdown is reported to have significantly changed bedtime for nearly 58% of children with ASD and rise time for 69% (Bruni et al, 2022 ). Various researchers have reported reduced sleep duration, difficulties in falling sleep, night waking, sleep terrors and daytime sleepiness in autistic populations (Bruni et al, 2021 , 2022 ; Reynaud et al, 2022 ; Türkoğlu et al, 2020 ); in addition, adults with autism displayed higher levels of sleep and circadian rhythm disturbances, with less favorable daily routines (Reynaud et al, 2022 ) and children with ASD reported higher presence of the ‘eveningness’ chronotype and higher autism symptom scores during the period of home confinement (Türkoğlu et al, 2020 ).…”
mentioning
confidence: 99%